Формирование комплексных расчетных моделей элементов штампов для разделительных операций - Ищенко, Ольга Анатольевна; Іщенко, Ольга Анатоліївна; Ishchenko, Olha; Ткачук, А. В.; Грабовский, А. В.; Демина, Наталья Анатольевна; Дьоміна, Наталя Анатоліївна; Domina, Natalia (My University, 2016)
RU: В статье описан новый подход к формированию расчетных моделей для элементов разделительных штампов. Предложено формировать комплексную модель, учитывающая условия силового и кинематического сопряжения базовых плит, пакета и направляющих колонок. В созданных моделях учтен множественный контакт элементов штампов. Также обеспечено построение параметрических моделей. Эти модели позволяют организовывать многовариантные расчеты напряженно-деформированного состояния. На основе анализа результатов этих расчетов определяются рациональные проектно-технологические параметры разделительных штампов. EN: The new approach in computable models formation for the shearing dies elements is described in the article. It has been suggested to form a comprehensive model which takes into account the conditions of power and kinematic connection between the base plates, the package and the guideposts. The designed models consider the multiple contacts between dies elements. The construction of the parameter-oriented models is also ensured. These models make it possible to organize multiple calculations of stress-strain state. It has been established that consideration of the contact interaction conditions significantly alter the results of the stress-strain state of the dies elements. A substantial disparity of the stresses distribution in the elements of dies was defined. Stress concentration zones have been identified. Maximum stresses which strongly nonlinearly depend on design parameters were revealed. Reasonable design and production parameters of the shearing die are determined after the analysis of the calculations results.
Formation of complex computable models of dies elements for shearing operations
Keywords: напряженно-деформированное состояние; разделительный штамп; базовая плита; расчетная модель; метод конечных элементов; the stress-strain state; shearing die; base plates; design model; finite-element method